2016
DOI: 10.1136/bmjdrc-2015-000184
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status and glycemic control in adult patients with type 2 diabetes: a mediation analysis

Abstract: ObjectiveThe purpose of this study is to examine the contribution of health behaviors (self-management and coping), quality of care, and individual characteristics (depressive symptoms, self-efficacy, illness representations) as mediators in the relationship between socioeconomic status (SES) and glycemic control.MethodsA sample of 295 adult patients with type 2 diabetes was recruited at the end of a diabetes education course. Glycemic control was evaluated through glycosylated hemoglobin (HbA1c). Living in po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 81 publications
5
67
2
Order By: Relevance
“…The high rate of illiteracy among the studied subjects with DM stands out. The prevalence of inadequate glycemic control was not associated with this variable in the final model, although the results may point to a more adequate control tendency when the level of education increases, corroborating the results of other studies (13)(14)(15)(16) which demonstrated that having a higher education level is associated with better glycemic control. One justification for this may be a tendency for people with a higher education level to be more concerned about adhering to the prescribed therapy, as well as to comply with the clinical recommendations proposed by the health team involved (12)(13) .…”
Section: Discussionsupporting
confidence: 87%
“…The high rate of illiteracy among the studied subjects with DM stands out. The prevalence of inadequate glycemic control was not associated with this variable in the final model, although the results may point to a more adequate control tendency when the level of education increases, corroborating the results of other studies (13)(14)(15)(16) which demonstrated that having a higher education level is associated with better glycemic control. One justification for this may be a tendency for people with a higher education level to be more concerned about adhering to the prescribed therapy, as well as to comply with the clinical recommendations proposed by the health team involved (12)(13) .…”
Section: Discussionsupporting
confidence: 87%
“…40,41 Similarly, a lack of association between PAM and a specific diet could be that the specific diabetes diet may be financially prohibitive. 42,43 These results highlight the importance of addressing all self-care domains to improve self-management for patients with comorbid diabetes and CKD across all spectrums of activation.…”
Section: Discussionmentioning
confidence: 94%
“…A possible reason for the lack of association between PAM and exercise and foot checking is that both these activities require a certain degree of physical fitness and ability, which is compromised in patients with diabetes and CKD due to comorbidity . Similarly, a lack of association between PAM and a specific diet could be that the specific diabetes diet may be financially prohibitive . These results highlight the importance of addressing all self‐care domains to improve self‐management for patients with comorbid diabetes and CKD across all spectrums of activation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, not perceiving oneself as sick might be interpreted as an avoidant coping strategy. Studies have shown that people with low socioeconomic status tend to use avoidant coping as their primary coping strategy due to few resources (Christensen, Schmidt, Hougaard, Kriegbaum, & Holstein, 2006;Houle et al, 2016;Mathiesen et al, 2017). The avoidant coping strategy of participants might have been reinforced by diabetes being a silent disease and, moreover, by the provision of tacit practical support from the informal network.…”
Section: Discussionmentioning
confidence: 99%